Digital Competences and Trends in Applications to Support Health Lifestyle - Rahayu, Nur Indri; Muktiarni, M; Ismail, Affero (Universitas Komputer Indonesia, 2023)
This research aims to analyze trends in researchers' behavior when researching sports applications to support a healthy lifestyle. Bibliometric analysis was used as a method in this research. Research data was collected via the Scopus page starting May 22, 2024. The keywords used were